Genome-wide co-localization of active EGFR and downstream ERK pathway kinases mirrors mitogen-inducible RNA polymerase 2 genomic occupancy. Issue 21 (1st September 2016) - Mikula, M.; Skrzypczak, M.; Goryca, K.; Paczkowska, K.; Ledwon, J.K.; Statkiewicz, M.; Kulecka, M.; Grzelak, M.; Dabrowska, M.; Kuklinska, U.; Karczmarski, J.; Rumienczyk, I.; et al.
Abstract: Genome-wide mechanisms that coordinate expression of subsets of functionally related genes are largely unknown. Recent studies show that receptor tyrosine kinases and components of signal transduction cascades including the extracellular signal-regulated protein kinase (ERK), once thought to act predominantly in the vicinity of plasma membrane and in the cytoplasm, can be recruited to chromatin encompassing transcribed genes. Genome-wide distribution of these transducers and their relationship to transcribing RNA polymerase II (Pol2) could provide new insights about co-regulation of functionally related gene subsets. Chromatin immunoprecipitations (ChIP) followed by deep sequencing, ChIP-Seq, revealed that genome-wide binding of epidermal growth factor receptor, EGFR and ERK pathway components at EGF-responsive genes was highly correlated with characteristic mitogen-induced Pol2-profile. Endosomes play a role in intracellular trafficking of proteins including their nuclear import. Immunofluorescence revealed that EGF-activated EGFR, MEK1/2 and ERK1/2 co-localize on endosomes. Perturbation of endosome internalization process, through the depletion of AP2M1 protein, resulted in decreased number of the EGFR containing endosomes and inhibition of Pol2, EGFR/ERK recruitment to EGR1 gene. Thus, mitogen-induced co-recruitment of EGFR/ERK components to subsets of genes, a kinase module possibly pre-assembled on endosome to synchronize their nuclear import, could coordinate genome-wide transcriptional events to ensure effective cell proliferation.